The correlation between parental communication pattern, self-esteem, and moral disengagement with cyberbullying behavior in early adolescents: A cross-sectional study - Dian octavia; Rian Maylina Sari; Diah Merdekawati; Rara Marisdayana; Rian Yuliyana (Jurnal Ners, 2022)
Introduction: Cyberbullying has become a new case in young millennials that can lead to being a serious problem if it is not faced properly. Many cases cannot be resolved because the victims did not tell the truth clearly to their parents and teachers. It may cause a lack of self-esteem among the students and also make the perpetrator become morally disengaged. The purpose of this study was to identify the correlation between parental communication patterns, moral disengagement, and self-esteem with cyberbullying behavior in junior high school. Methods: A cross-sectional study was performed with 362 junior high school students in Indonesia using purposive sampling. Variables in this study were moral disengagement, self-esteem and parental communication patterns with cyberbullying behavior. The data were collected with the Rosenberg self-esteem scale, the cyberbullying behavior scale, the moral disengagement scale and the family communication pattern scale. Bivariate analysis with Chi-square was used to analyze the data. Results: This study found out that there were 223 students, 61.6% were female, and 43.6% were aged 14 years. There were 187 students (51.7%) who had mild cyberbullying behavior. The study revealed that there were significant correlations among cyberbullying behavior with moral disengagement (p = 0.005, self-esteem (p = 0.008), and parental communication pattern (p = 0.019). Conclusions: Parental communication, moral disengagement and self-esteem have a correlation with cyberbullying behavior. It was expected that the schools need  to implement a training to improve social skills in junior high school students.